A Systematic Review on the Climate and Ecosystem Change Associated With the COVID-19 Epidemic: Global Challenges - Mehran Maleki Roveshti; Farahnaz Khajehnasiri; Elham Akhlaghi Pirposhteh; Nasir Amanat; Ali Salehi Sahlabadi; Javad Vatani; Mohsen Poursadeqiyan (Hamadan University of Medical Sciences, 2022)
The most serious current challenge in the world is COVID-19 disease incidence. With the spread of COVID-19, in addition to widespread human and economic damages, concerns have increased about the world's climate and ecosystem change. This change alters the genetic structure of viruses, leading to newer strains. This study addressed global challenges regarding the COVID-19 epidemic effects and possible two-way changes in climate and ecosystems. Studies conducted from 2019 to 2022 were reviewed in this systematic review. Articles on climate and ecosystem change related to the COVID-19 epidemic were searched in the Scopus, Web of Science, and PubMed databases in accordance with the MeSH search strategy using keywords such as "Climate Change" and "Ecosystem" or "COVID-19". In this research, the coding method based on the PRISMA chart was used, and 13 related articles were included in the study after qualitative evaluation. The COVID-19 epidemic is likely to have significant implications for progress in climate and ecosystem change. The phenomenon of climate change and its interaction with the COVID-19 epidemic is not limited to natural issues. One of the most important consequences is its impact on the social and economic issues of human societies, the most important of which are air pollution and environmental degradation. An increase in normal and special wastes, water consumption and wastewater production, air pollution after the start of the global economy, damage to forests and animals, and tendencies to use fossil fuels are only a part of the direct and indirect negative effects of COVID-19 on climate and ecosystem change. Epidemics directly threaten people and the health system, while climate and ecosystem change more broadly weakens natural and human systems. The COVID-19 crisis requires solutions within weeks and months, whereas responses to the climate and ecosystem change crisis seem less acute. However, the effects of climate and ecosystem change worsen with further procrastination. Thus, such crises with overlapping conditions and interactions require more attention and immediate public mobilization. Thus, the necessary planning should be implemented to moderate and reduce its effects.